Relationship Between Zooplankton Community with Water Quality in Ebony Lake, Pantai Indah Kapuk, North Jakarta: Hubungan Antara Komunitas Zooplankton dan Kualitas Air di Perairan Danau Ebony, Pantai Indah Kapuk, Jakarta Utara - Majariana Krisanti; Sigid Hariyadi; Hilman Hidayat; Dwi Yuni Wulandari (Habitus Aquatica, 2021)
Ebony Lake is an ornamental lake, where its surrounding domestic activity which can produce waste that may affect water quality including organism in there, such as zooplankton. Ebony Lake has become the study object to see correlation between zooplankton community and water quality. This research had been done between April-August 2014 in 5 station every month. Zooplankton community in Ebony Lake consists of the phylum Rotifera, Crustacea, and Protozoa. The highest abundance of zooplankton is Brachionus from Rotifera. The phylum Rotifera has a strong negative correlation with TSS, turbidity, and ammonia, whilst it has strong positive correlation with acidity/pH. The high value of TSS, turbidity, and ammonia, followed by the low abundance of Rotifers; while low pH will be followed by high abundance of Rotifers. The phylum Protozoa has a strong positive correlation with TSS and negative with temperature.